50 ways to use technology enhanced learning in the classroom practical strategies for teaching - Atherton, Pete (London Learning Matters/SAGE, 2018)
This is a practical guide to the use of technology enhanced learning (TEL) in the classroom. Introducing 50 ways to use technology for learning. Areas covered include: Gamified learning; Social media; Video streaming; The flipped classroom; Instant feedback tools; And many more. Guidance on how to use these technologies for learning is complemented by an exploration of their impact on learning. For each example, the opportunities for evidencing progress are evaluated -- Provided by the publisher.
Edtech will always change...quickly. Formative assessment in the digital age ; Gamification ; The flipped classroom ; Bring your own device (BYOD) ; Social media literacies -- Emerging tech. Artificial intelligence (AI) in education: Virtual reality (VR) -- Assessment/assignment tools. WISEflow ; Comparative judgement: No more marking ; Spiral ; Goformative ; A Tale Unfolds ; Book Creator ; VoiceThread ; AnswerGarden ; Nearpod ; Turnitin -- Social media. Facebook ; Twitter ; Snapchat ; Instagram ; Tumblr ; Pinterest ; Learnium -- Video and audio tools. H5P ; YouTube ; EDpuzzle ; TuitionKit ; Panopto ; Podcasting: Audacity and GarageBand -- Collaborative working. Padlet ; QR codes ; G Suite for education ; Lino ; Popplet ; MindMapfree ; WordPress ; Notability -- Games, polls and student response systems. Slido ; Kahoot! ; Quizlet ; GoSoapBox ; Poll Everywhere ; Plickers ; ClassDojo -- Presentation platforms. Explain Everything ; Infographics ; Canva ; PowerPoint ; iSpring.
Includes bibliographical references and index.
Keywords: Educational technology; Computer-assisted instruction; Teaching -- Aids and devices; Internet in education; Learning